Subjective Well-Being and Burnout Among the Maternal and Child Health Workforce - Carolyn Brown-Kaiser; Amita Vyas (SAGE Publishing, 2024)
Objectives: This study investigates burnout and subjective well-being among the Maternal and Child Health (MCH) workforce, considering recent events such as the Dobbs decision, the maternal mortality crisis, and the COVID-19 pandemic. Methods: An anonymous web-based, cross-sectional survey was conducted among 313 MCH professionals in the United States. Data were collected using validated measures, including the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) and the Oxford Happiness Questionnaire (OHQ) short scale. Sociodemographic characteristics and factors associated with burnout and subjective well-being were examined using univariate statistics and multivariable models. Results: Analysis revealed moderate levels of burnout among MCH professionals, particularly in emotional exhaustion. However, subjective well-being levels were relatively high. After controlling for covariates, significant associations were found between subjective well-being and burnout dimensions, as well as sociodemographic factors such as sex and race. Conclusions: The study's findings indicate that higher subjective well-being is significantly associated with lower burnout, emotional exhaustion, and higher personal accomplishment. Variations in burnout and well-being are also influenced by sociodemographic factors such as age, sex, race, and occupation. Tailored interventions addressing the specific needs of MCH professionals are essential for building a resilient workforce. Organizational reforms and legislative measures are crucial for fostering supportive workplace environments and ensuring access to care and services amidst workforce challenges.